Solve the equation 5x-1+11x=65x-36

11x+5x-1=65x-36

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

$x=\frac{5}{7}$

Step by step solution

Problem

$11x+5x-1=65x-36$
1

Adding $11x$ and $5x$

$16x-1=65x-36$
2

Grouping terms

$-65x-1+16x=-36$
3

Adding $16x$ and $-65x$

$-49x-1=-36$
4

Subtract $-1$ from both sides of the equation

$-49x=1-36$
5

Subtract the values $1$ and $-36$

$-49x=-35$
6

Multiply both sides of the equation by $$

$x=\frac{5}{7}$

Answer

$x=\frac{5}{7}$

Struggling with math?

Access detailed step by step solutions to millions of problems, growing every day!

Problem Analysis

Main topic:

Equations

Time to solve it:

0.27 seconds

Views:

93